Zagadnienia konstrukcyjne umów publicznoprawnych - Staniszewska, Lucyna (Studia Prawa Publicznego, 2019)
The formulation of legal provisions by the administration does not have to take the form of administrative decisions. One of the legal forms of the administration is public-law contracts. This is one of the forms of administration which still requires a further scientific analysis. Contracts are useful instruments, and therefore it may be worth looking at their different types and construction. They may be classified according to the parties to the legal relationship created. There are two types of contracts, i.e. between administrative bodies and between an administrative body and an entity. The doctrine refers to contracts of the latter type as administrative and legal agreements. Such agreements have developed in the Polish legal order after the systemic changes. Unfortunately, the legislator has not provided their legal definition, they are regulated in special laws, most often by indicating contractual provisions constituting essentialia negotii. The doctrine does not explicitly define the character of the contracts concluded by the administrative body and its contractor, nor has the final characteristics of the content of contracts in the administration as a whole been made. There is still a lack of consensus as to the construction of public law contracts and the rules governing them. There is an urgent need to regulate the essence of administrative contracts, and in particular to indicate their construction and legal nature, in order to better protect legal entities entering into them. The purpose of public-law contracts is to improve the quality of administration, and increase the efficiency of administrative activities. More administrative contracts also mean higher decentralisation of the state. Moreover, the idea of extending the use of public-law contracts is consistent with the principle of the participatory role of citizens in achieving public effects. The Polish legislator may draw on the regulations of other countries, for instance Germany, where public-law contracts have received legal definitions.